THE MOTIVATION AND THEIR EFFECT ON TEACHER PERFORMANCE: THE MEDIATION ROLE OF WORK EXPERIENCE - Wahyudi, Yuda Putra; Armanu, Armanu; Suryadi, Nanang (Universitas Brawijaya, Indonesia, 2023)
This study aims to analyze the effect of motivation on performance mediated by work experience. Teachers at State Junior High Schools are the population in this study. The sampling technique used a purposive sampling method with 321 teachers as respondents. The technique used is Partial Least Square. The analysis results show that: Motivation has a significant positive effect on performance; Motivation has a significant positive impact on work experience; Work experience has a significant positive effect on performance; Work experience significantly mediates the effect of motivation on performance. The implication of this research is to have a suitable influence on motivation the public junior high school teachers in the Malang district should continue to be encouraged by using an approach to success expectations, value implications and potential costs of implementing professional development so that they always have motivation at work. Expectations of success, value implications, and potential costs of implementing professional development will be met. Teachers can play a role in terms of providing support. Teachers have more enthusiasm and encouragement in their work and can show performance. Work experience can also act as a mediating variable; principal collaboration and partnerships with out-of-school institutions are forged, and learning collaboration supports performance. Motivation provides encouragement and efforts to do work to contribute to new work experiences and individual performance towards organizational performance.